Optimalisasi Unit Peremukan Dalam Pencapaian Target Produksi 60.000 Ton/Bulan Batu Granit pada Pt Vitrama Properti di Desa Air Mesu Kabupaten Bangka Tengah: Optimalization of Crushing Plant in Achieving The Production Target of 60.000 Tons/month Granite in PT Vitrama Properti at Air Mesu Village Central Bangka Regency - Setiawan, Ahmad Reza; Tono, E.P.S.B Taman; Indriawati, Anisa (MINERAL, 2018)
Granite crushing plant in PT Vitrama Properti is divided into two units, namely primary crusher and secondary crusher with production targets at 60,000 tons/month, but production target had not been reached. Therefore, to achieve the production target, it was necessary to analyze the optimalization of the crushing process starting from the assessment of the availability, the working efficiency of the operator, the feed rate and production capacity of crushing plant by using statistical and mathematical methods. In September 2016, the actual working efficiency of primary crusher unit and secondary crusher unit were very low at 15,75 % and 24,75 % with production only amounted to 16771.49 tons/month and 16,135,59 tons/month. The efforts undertaken in order to achieve production targets are: 1) Increase the actual working efficiency in the primary crusher previously 15,75 to 83.14%, while the secondary crusher previously 24,75 % to 83.27 % 2) Increase the feed rate to the secondary crusher previously 283,44 tons/hour to 320 tons/hour.